2014
DOI: 10.1103/physrevlett.113.085502
|View full text |Cite
|
Sign up to set email alerts
|

Self-Replicating Cracks: A Collaborative Fracture Mode in Thin Films

Abstract: Straight cracks are observed in thin coatings under residual tensile stress, resulting into the classical network pattern observed in china crockery, old paintings or dry mud. Here, we present a novel fracture mechanism where delamination and propagation occur simultaneously, leading to the spontaneous self-replication of an initial template. Surprisingly, this mechanism is active below the standard critical tensile load for channel cracks and selects a robust interaction length scale on the order of 30 times … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 24 publications
(42 reference statements)
1
63
0
3
Order By: Relevance
“…[37] and subsequently used, for example, in Refs. [13,26,27]. It is briefly recalled here for self-containedness.…”
Section: Setup and Main Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[37] and subsequently used, for example, in Refs. [13,26,27]. It is briefly recalled here for self-containedness.…”
Section: Setup and Main Equationsmentioning
confidence: 99%
“…They are observed during the desiccation of films made of colloidal suspensions, like bentonite clay or cornstarch [5][6][7][8][9][10][11], in sol-gel films [12,13], in broken objects like windows [14][15][16], or in sea ice [17,18] and ice floes collisions [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, crack-patterning has emerged as an alternative and convenient « bottom-up » method to pattern thin films. [4] In controlled conditions, crack propagation can proceed following straight, oscillatory or spiral-like paths [5] and/or it can be guided by micronotches (made by lithographic techniques) toward complex patterns and devices. [6] Alternatively, as observed in mud's cracks, Allain and Limat [7] demonstrated that controlled drying of colloidal droplets resulted in the formation of parallel periodic cracks oriented by the evaporation front-line.…”
mentioning
confidence: 99%
“…Although a large variety of patterns can be observed for different triggering conditions [24], we focus in this paper on the paradigm case of duos of cracks In this particular example, the cracks initially linked by a narrow delamination front, start to diverge but quickly converge towards a steady width W 2 . The pictures are taken with a constant time lap of 2 s. (b) Opposite case where the initial width is larger than W 2 , leading to the same optimal width.…”
Section: Duos Of Cracks: Experimental Observationsmentioning
confidence: 99%
“…Several failure modes compete in the sector of the diagram where e > Γ 0 i and e > Γ 0 c /2γ. Complex fracture patterns such as spiral and oscillatory paths resulting from "follower cracks" can indeed be observed [24] in addition to the the fracture and adhesion energy, and γ a numerical prefactor that depends on the mismatch of material properties between the substrate and the coating. The x-axis corresponds to the comparison of the residual energy density to the interfacial energy, whereas the y-axis compares residual elasticity to the material toughness.…”
Section: Stability Diagrammentioning
confidence: 99%